Complement in human reproduction: activation and control - Rooney, I A; Oglesby, T J; Atkinson, J P (Immunologic research, 1993)
The behaviour of the complement system during human reproduction is now the focus of much scientific attention. The presence of antisperm antibodies in the reproductive tracts of some infertile individuals, and of complement in cervical and ovarian follicular fluid, suggests that complement-mediated damage of spermatozoa is involved in some cases of infertility. Further, deposition of maternal IgG and of complement in the extrafetal tissues indicates that complement activation occurs within the fetoplacental unit. Recently, three complement-regulatory proteins--decay-accelerating factor, membrane cofactor protein and CD59--have been detected on spermatozoa and in the extrafetal tissues. It is likely that these inhibitors are essential for normal reproductive function. This article reviews current understanding of the interaction of the complement system with cells and tissues involved in reproduction, with emphasis on the nature and function of the controlling proteins.